Analysis of Research in Adoption of Person-Centred Healthcare Systems: The Case of Online Personal Health Record - Najaftorkaman, Mohammadreza; Ghapanchi, Amir Hossein; Talaei-Khoei, Amir (ACIS, 2014)
Although the personal health record (PHR) has enormous potential to ameliorate both documentation of health-related information and care of individuals, it has not been adopted as originally expected. The purpose of this paper is to analyse research studies in PHR adoption and provide a comprehensive taxonomy of the factors affecting PHR adoption. We searched three categories of key terms across nine academic databases and identified an initial set of 7,468 research studies. We filtered papers on the basis of their title, abstract and full text (91 remaining papers) to have relevant PHR adoption research studies. Based on the conceptualisation of adoption factors in the 91 included papers, a list of factors that impacted on PHR adoption was identified and we categorised them into six main clusters. This review is a good starting point for researchers who are interested in adoption of PHR systems. Furthermore, it provides valuable information for healthcare practitioners and PHR system developers.